New directions in hospitality and tourism : annual review of hospitality and tourism trends - Teare, Richard; Bowen, John (John T.), 1948- (Cassell, 1997)
This annual publication offers a concise overview and commentary on the emerging themes portrayed in British and American literature and research in the field of hospitality and tourism. It makes use of the wide range of reports emanating from UK industry, analysts, consulting firms, trade and professional associations, and government organizations. The commentary draws extensively on hundreds of articles published between 1989 and 1995 in a select group of European and American journals. This unique resource forms an ideal reference point for academics and practitioners interested in the 'big picture' as well as the details relating to new developments across industry sectors and specialisms.